The rejuvenation of urban community in China under COVID-19 - Xie, Linjun; Shao, Mengqi (Frontiers in Sustainable Cities, 2022)
The persistent COVID-19 pandemic has continuously brought the basic level of urban governance to the forefront. Urban community governance in China involves both state-led and civil society-led governance. Whilst previous studies have noted the weak civil society and delocalization in modern China, recent research reveals the re-localization trend shown during the pandemic. In this brief research report, we seek to provide a detailed account of the hyper-local dynamism within civil society in responding to the public health emergency, focusing on the thriving spontaneous groups in Shanghai during the COVID-19 outbreak in March and April 2022. By dissecting the multi-level, multi-actor governance, we reveal the significant roles played by spontaneous groups in complementing state-led governance and in building united urban communities in combatting the worst effects of COVID-19. We outline the types and organizational structure of various spontaneous groups. We also critically reflect on their implications and potential in advancing urban community governance in China. We argue that there is an imperative need to further explore how these spontaneous groups can catalyse transformative changes that can for example empower grassroots actors and motivate wider public participation in community decision-making.